Early Functional Outcomes After Evolutionary Total Knee Arthroplasty: A Randomized Controlled Trial. Is New Always Better?. Issue 3 (July 2021) - Panchani, Sunil K.; Divecha, Hiren M.; Lafferty, Rebecca; Pavlou, George; Oakley, Jez; Shaw, Debbie; Chitre, Amol; Wynn Jones, Henry; Raut, Videsh; Smith, Robert; Gambhir, Anil; Board, Tim
Abstract : Background: Total knee replacement (TKR) designs continue to evolve with the aim of improving patient outcomes; however, there remains a significant patient dissatisfaction rate. We report the early functional outcomes of an evolutionary knee design in the context of a single-blinded, noninferiority, randomized controlled trial. Methods: Patients were randomized to receive either the P.F.C. SIGMA or ATTUNE knee implant systems (DePuy Synthes). All implants were fixed-bearing, cruciate-retaining, and cemented constructs. Patients were assessed at baseline and 6 weeks, 3 months, and 1 year postoperatively using clinical and functional outcome measures, including range of motion, Oxford Knee Score (OKS), Oxford Knee Score-Activity and Participation Questionnaire (OKS-APQ), Patient Knee Implant Performance (PKIP) score, 5-Level EuroQol 5 Dimensions (EQ-5D-5L), and Short Form-36 outcome measures. Results: There were 150 patients who underwent a surgical procedure (76 with the ATTUNE implant and 74 with the P.F.C. SIGMA implant), with 147 patients remaining at the final review. No differences were observed in any of the outcome measures between the groups at any time point. Tourniquet time was significantly shorter in the P.F.C. SIGMA arm (p = 0.001); however, this had no clinical impact on the OKS (analysis of covariance [ANCOVA] test) at the final review (p = 0.825). There was no difference in the numbers of patients achieving the minimal clinically important difference for the OKS between the groups (p = 0.817). Conclusions: This trial did not show inferiority of the ATTUNE implant when compared with the P.F.C. SIGMA implant. The authors believe that implant innovation should continue and that modern implants should be introduced into the market following randomized controlled trials. Further work should assess the effect of non-implant-related factors on patient outcomes. Level of Evidence: Therapeutic Level I . See Instructions for Authors for a complete description of levels of evidence.